2006
DOI: 10.1179/146531205225021492
|View full text |Cite
|
Sign up to set email alerts
|

Psychological support for orthognathic patients – what do orthodontists want?

Abstract: Although we have no evidence to prove that interdisciplinary care is better for patients, clinical experience and reports from clinicians working in large centres, tells us there are probable advantages. The development of a training programme for both orthodontists and mental health teams would seem to be beneficial for both clinicians and patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 19 publications
0
24
0
3
Order By: Relevance
“…33 Patients undergoing orthognathic treatment must receive appropriate psychological support 7,34,35 and should be informed about a possible psychological impact of treatment. [36][37][38][39] As is seen in the results of many studies, 40,41 orthognathic treatment should start with psychological testing of patients. Psychological evaluation in orthognathic treatment planning has the same importance as that in soft tissue and skeletal analysis.…”
Section: Discussionmentioning
confidence: 99%
“…33 Patients undergoing orthognathic treatment must receive appropriate psychological support 7,34,35 and should be informed about a possible psychological impact of treatment. [36][37][38][39] As is seen in the results of many studies, 40,41 orthognathic treatment should start with psychological testing of patients. Psychological evaluation in orthognathic treatment planning has the same importance as that in soft tissue and skeletal analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The role of psychology is raised in a number of studies in relation to supporting patients during the treatment process, but less attention has been paid to the potential to enhance or provide an alternative to medical treatment for issues such as appearance concern, social anxiety, and self-esteem problems. It has been suggested that clinicians may fear negative reactions from patients if they suggest referral to a mental health professional (Juggins et al, 2006), but contrary to this a study of patient views showed that 95.2% would welcome this input (Ryan et al, 2009).…”
Section: Discussionmentioning
confidence: 93%
“…Data protection and ethical approval (reference number Z6364106/2018/08/46) were granted from UCL Data Protection and Ethics Committees and a 'Privacy Notice' was placed at the start of the questionnaire in compliance with the General Data Protection Regulation. The questionnaire was developed through a number of different approaches, starting with the eight-item questionnaire utilised by Juggins et al (2006) and building on that through a thorough search of the literature, discussions within the research team and with other interested parties; a 25-item questionnaire was developed using this approach. The questionnaire was divided into five main areas:…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, 30.5% of respondents did not refer any orthognathic patients, as they had nobody to refer to. Juggins et al (2006) identified a lack of training experience in the UK; 80.8% of the respondents had no formal teaching in psychological assessment/ management of orthognathic patients. The importance of providing appropriate training in these areas has been recognised more recently in the Post CCST training guidelines (Joint Committee for Postgraduate Training in Dentistry Specialty Advisory Committee in Orthodontics, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation